Ethnography and comparative education: some contemporary trends and critical issues - Paolone , Anselmo (Rivista di Storia dell’Educazione, 2018)
The paper attempts a brief analysis of two of the areas in which ethnographic research can make today an important contribution to comparative education. Ethnography can not only help to outline a descriptive picture of what contemporary education is around the world. Ethnography can also work (both in terms of the “alternative” data it can gather, and of the insights it can inspire in debates on comparative education, via its peculiar approach to knowledge and its rich and diverse epistemological tradition) as a tool to help comparative education to solve some of its contemporary dilemmas.